Effects of Sex and Diet on Gut Microbiota of Farmland-Dependent Wintering Birds - Liu, Gang; Meng, Derong; Gong, Minghao; Li, Huixin; Wen, Wanyu; Wang, Yuhang; Zhou, Jingying (Frontiers in Microbiology, 2020)
Gut microbiota plays an important role for bird biological and ecological properties, and sex and diet may be important intrinsic and extrinsic fators influencing gut microbial communities. However, sex difference of gut microbiota has been rarely investigated in free-living birds, and it remains unclear how sex and diet interactively affect avian gut microbiota compostion and diversity, particularly under natural conditions. Here we used non-invasive molecular sexing technique to sex the fecal samples collected from two wintering sites of Great Bustard, which is the most sexually dimorphic among birds, as well as a typical farmland-dependent wintering bird. High-throughput sequencing of 16S was applied to identy the gut microbiota commuties for both sexes under two different diets. The results showed that a certain proportion of common microbiota taxa was shared among defined groups, revealing the conservatism of gut microbiota. Microbiota diversity, composition and abundance varied on different diets for male and female Great Bustards, suggesting that the gut microbiota was interactively influenced by both sex and diet. Under the wheat_corn diet, females had higher abundances of the phylum Verrucomicrobia than the male, but lower Bacteroidetes and Firmicutes compared to the male; meanwhile, the microbiota diversity and evenness were higher for males than females. In contrast, under the rice_peanut diet, females were more colonized by the phylum Firmicutes than males, but less by the phylum Bacteroidetes; while males had lower microbiota diversity and evenness than females. It suggests that diet-based shifts in the host gut microbiota might benefit the Great Bustard by helping the host adapt to the local environment. Future conservation should consider differences in overwintering food resources, which influence the nutritional quality of both the diet and associated microbiota.